2019
DOI: 10.1002/aenm.201802856
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Fe‐Doped MOF‐Derived Carbon Polyhedrons with High Active‐Center Density and Ultra‐High Performance toward PEM Fuel Cells

Abstract: A metalorganic gaseous doping approach for constructing nitrogen‐doped carbon polyhedron catalysts embedded with single Fe atoms is reported. The resulting catalysts are characterized using scanning transmission electron microscopy, X‐ray photoelectron spectroscopy, and X‐ray absorption spectroscopy; for the optimal sample, calculated densities of Fe–Nx sites and active N sites reach 1.75812 × 1013 and 1.93693 × 1014 sites cm‐2, respectively. Its oxygen reduction reaction half‐wave potential (0.864 V) is 50 mV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(113 citation statements)
references
References 32 publications
8
103
0
1
Order By: Relevance
“…[19,20] Compared with traditional ironbased materials, the Fe atoms of MOFs, which are bonded by organic ligands, are maximally dispersed, and there is ample presence of confined iron sites. [21,22] Despite the high activity and good sulfur resistance of the iron sites, these catalysts are restricted in application because they are water sensitive and time consuming to prepare. [23,24] Thus, it is highly desirable to find a rational way to design isolated iron sites (Fe-Oχ and/or Fe-Nχ) to address the problems of traditional iron-based catalysts.…”
Section: Iron-based Catalysts Have Been Widely Studied For the Oxidatmentioning
confidence: 99%
“…[19,20] Compared with traditional ironbased materials, the Fe atoms of MOFs, which are bonded by organic ligands, are maximally dispersed, and there is ample presence of confined iron sites. [21,22] Despite the high activity and good sulfur resistance of the iron sites, these catalysts are restricted in application because they are water sensitive and time consuming to prepare. [23,24] Thus, it is highly desirable to find a rational way to design isolated iron sites (Fe-Oχ and/or Fe-Nχ) to address the problems of traditional iron-based catalysts.…”
Section: Iron-based Catalysts Have Been Widely Studied For the Oxidatmentioning
confidence: 99%
“…It was demonstrated that high activity originates from the facile electron transfer from single Fe atoms in the specific FeN 4 configuration, accelerating the rate determining *OH to OH − formation step on Fe–N–C catalysts. To synthesize Fe–N–C electrocatalysts with uniform distribution and high Fe content, ZIFs and MOFs have been rationally engineered by incorporating Fe atoms through intrinsic ionic coordination and pore confinement strategies, or postprocessed to trap Fe atoms with the help of intrinsic N atoms 61c,62,64a,86. For instance, Fe–N–C catalysts were synthesized via coordinating Fe atoms with ligands in Zn‐based imidazolate framework and subsequently converting them into porous Fe‐ and N‐doped carbon materials through thermal activation 61c.…”
Section: Energy‐related Applicationsmentioning
confidence: 99%
“…A MOF-derived doped-carbon catalyst with a high density of active sites/single Fe atoms, optimized porosity, and high surface area was prepared by Deng et al [ 69 ] using a metallorganic gaseous doping strategy. Ferrocene (Fe source) was vaporized and trapped into a ZIF-8 host structure, and, together with the organic skeleton, it was pyrolyzed at 950 °C to yield a highly porous carbon-based catalyst with single Fe atoms coordinated by N on the carbon skeleton.…”
Section: Mof-based Orr Electrocatalystsmentioning
confidence: 99%